ChemInform Abstract: Oxime Ligation: A Chemoselective Click‐Type Reaction for Accessing Multifunctional Biomolecular Constructs. Issue 11 (18th March 2014) - Ulrich, Sebastien; Boturyn, Didier; Marra, Alberto; Renaudet, Olivier; Dumy, Pascal
Abstract Review: 73 refs.